Potassium and Thorium Abundances at the South Pole‐Aitken Basin Obtained by the Kaguya Gamma‐Ray Spectrometer. Issue 9 (2nd September 2019) - Naito, M.; Hasebe, N.; Nagaoka, H.; Wöhler, C.; Berezhnoy, A. A.; Bhatt, M.; Kim, K. J.
Abstract: In this study, we present detailed K and Th distribution maps of the South Pole‐Aitken (SPA) basin with a (100‐km) 2 resolution for the compositional and evolutional studies. These maps have been constructed for the first time from the Kaguya gamma‐ray spectrometer (KGRS) data sets acquired during SELENE (Kaguya) low‐altitude observations at 50 km. The K and Th distribution maps are compared with those obtained by KGRS high‐altitude observation and Lunar Prospector GRS high‐ and low‐altitude observations. The use of KGRS low‐altitude data sets with high energy resolution enable to obtain unambiguous counts of individual gamma‐ray lines, leading precise elemental maps of K and Th comparing to previous studies. K and Th abundances at the areas of some large impact craters infilled with mare deposits are lower than that in surrounding regions. Geologic maps of the SPA region obtained by the Kaguya Multiband Imager are assimilated and confirmed based on the K and Th distributions. The evolution hypothesis of the SPA region based on the SPA giant impact event suggested by some previous model studies is also confirmed. Plain Language Summary: Detailed K and Th distribution maps around South Pole‐Aitken (SPA) basin at lunar southern pole were obtained by the Kaguya gamma‐ray spectrometer data sets. Incompatible elements such as K and Th are important to investigate the lunar mantle and crust since they remain as liquid until the final stage of crystallization. Our K and Th maps implies the large SPA forming impact event led to ejection of K and Th rich materials, enhancing K and Th at SPA region. The SPA impact also caused convection of K and Th rich liquid layer toward the lunar nearside, resulting a depletion of these elements beneath SPA region. Key Points: Detailed potassium and thorium abundance maps at South Pole‐Aitken region are constructed with the Kaguya gamma‐ray spectrometer data sets Composition and evolution of the South Pole‐Aitken were compared and discussed with Kaguya Multiband Imager insterument results Analysis of the K and Th maps gives details about ejection and convectional transport of urKREEP layer from the lunar farside to nearside